Histomorphic Analysis of UV-C Radiation on Osseointegration of Titanium Implants in the Rabbits - Reza Vafadoost; Mohamad-Reza Shabahangfar; Ahad Khoshzaban; Hamid Ahmadian-Moghadam (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Unsuccessful implant integration leads to pain and implant mobility. Implant photo-functionalization by ultraviolet (UV) light has been suggested as a method that may stimulate osseointegration  Purpose: This study was conducted to analyze the histopathological feature of the titanium implant surface upon treatment with UV-C wave.Materials and Method: In this interventional study, twenty rabbits were enrolled. In the treatment groups, the titanium implants, irradiated earlier with UV-C for four hours laterally, were inserted in one of the femur bones. In the control group, the titanium implants without irradiation were inserted in the other femur bone of the rabbits. After two and four weeks, the animals were sacrificed, and then the samples were histologically and histo-morphometrically analyzed. In addition, the amounts of new bone formation, bleeding, and inflammation were recorded, and the data were subjected to statistical analysis.Results: The results confirmed that UV-C irradiation to titanium implants significantly improved new bone formation (p< 0.001). However, no significant new bone formation was observed between two and four weeks after implant insertion (p< 0.098).Conclusion: The study results showed that irradiating titanium implants with UV-C for four hours significantly improves osseointegration and new bone formation but does not considerably affect inflammation or bleeding around the implant. The study suggests that UV-C radiation can increase the success rate of implant treatment.